Erratum - Rylands, Anthony B.; Luna, Ernesto Rodríguez (Neotropical Primates, 1996)
In the first article of Neotropical Primates 3(4), December 1995, the name and address of the author was unfortunately omitted. The author was Thomas J. Masterson of the Department of Biology, James Madison University, Harrisonburg, Virginia 22807, USA. The correct citation for this article is as follows: Masterson, T. J. 1995. Morphological relationships between the Ka’apor capuchin (Cebus kaapori Queiroz,1992) and other male Cebus crania: a preliminary report. Neotropical Primates 3(4): 165-169. The editors apologize for this error.